Oncoplastic Augmentation Mastopexy in Breast Conservation Therapy: Retrospective Study and Postoperative Complications. Issue 1 (January 2023) - Salinas, Harry M.; Ainuz, Bar Y.; Pourmoussa, Austin J.; Levitt, Eli B.; Ali, Aleeza; Bouz, Antoun; Treiser, Matthew D.; Medina, Miguel A.
Abstract : Background: Oncoplastic techniques, in conjunction with lumpectomy and adjuvant radiotherapy, have been demonstrated to achieve good aesthetic results and cancer outcomes in the treatment of patients with macromastia or significant ptosis. This study evaluated a series of patients undergoing breast conservation with concomitant oncoplastic-augmentation-mastopexy and a contralateral augmentation-mastopexy. Methods: Patients undergoing lumpectomy for breast conservation were identified via a retrospective chart review. Inclusion criteria included patients with ptosis and preexisting breast implants or insufficient breast volume undergoing oncoplastic implant placement/exchange and mastopexy. Demographic characteristics, operative details, and complications were assessed. Results: Thirty-four consecutive patients (64 breasts, 4 unilateral procedures) were included in the study. Average age was 51.4 years, average body mass index was 27, and 38.2% were smokers/former smokers. The average operative time was 2.5 hours. Furthermore, 38.2% of patients received chemotherapy, and 82.4% of patients received breast adjuvant radiotherapy. The average length of follow-up was 11.7 months. In the sample that received radiation, the capsular contracture rate was 25%, with a 7.1% contracture revision rate. For the entire group, a total of 8 patients (23.5%) underwent revisions for either positive margins (8.8%), capsular contracture (8.8%), implant loss (2.9%), or cosmetic concerns (2.9%). One patient developed a pulmonary embolism. Conclusions: Oncoplastic-augmentation-mastopexy is a safe technique with acceptable complication rates. This technique is best used for breast cancer patients with breast ptosis and a paucity of breast volume or preexisting implants who wish to pursue breast-conserving therapy. The revision rates are acceptable compared with single-stage cosmetic augmentation procedures as well as other oncoplastic techniques described in the literature, but patients must be clearly counseled on contracture risk.